Time of change: Health effects of motherhood - Fabian Dehos; Marie Paul; Wiebke Schäfer; Karolin Süß (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This paper combines German claims and survey data to provide a comprehensive picture of the health dynamics surrounding the transition into motherhood. Event-study estimates reveal good mental health around birth, but declines afterward, as reflected by increasing mental illness diagnoses and antidepressant and psychotherapy use during the first four years of motherhood. Painkillers, headaches, obesity, and other potentially stress-related physical illnesses, as well as survey evidence on well-being, show a similar pattern. A sustained reduction in sleep, sports, and other leisure activities, coupled with childcare obligations and possible psychosocial distress, may contribute to the long-term adverse effects of motherhood. – – Das vorliegende Diskussionspapier kombiniert deutsche Abrechnungs- und Umfragedaten, um ein umfassendes Bild der Gesundheitsdynamik rund um die Mutterschaft darzustellen. Event-Study-Schätzungen zeigen eine gute psychische Gesundheit unmittelbar vor und nach der Geburt, gefolgt vor einer anschließenden Verschlechterung, die sowohl durch die Zunahme von Diagnosen psychischer Erkrankungen als auch die verstärkte Nutzung von Antidepressiva und Psychotherapie in den ersten vier Jahren der Mutterschaft gekennzeichnet ist. Schmerzmittel, Kopfschmerzen, Fettleibigkeit und andere potenziell stressbedingten körperlichen Erkrankungen sowie Befragungen zum Wohlbefinden zeigen ein ähnliches Muster. Eine anhaltende Reduktion von Schlaf, Sport und anderen Freizeitaktivitäten, verbunden mit erhöhter Kinderbetreuung und möglichem psychosozialen Stress, könnte zu den langfristigen negativen Auswirkungen der Mutterschaft beitragen.
Keywords: J13; I10; I12; 330; Maternal health; mental health; claims data